#Follow: exploring the role of social media in the online construction of male sex worker lives in Dublin, Ireland. Issue 12 (1st December 2016) - Ryan, Paul
Abstract: This article draws from qualitative interviews with 18 South American male sex workers in Dublin, exploring how their use of the gym and new social media has created alternative spaces for the conduct of commercial sex. The interviews reveal how sex workers alternatively use escort specific sites in conjunction with mainstream dating apps like Grindr, offering greater flexibility and control over how they are self-defined within the sex industry. These male sex workers become known for their presence in gyms and clubs within the small gay community offering potential clients a real-time embodied interaction. Social media, like Instagram, offered the men in this study a further platform to share part of a choreographed online world with thousands of followers presenting new economic opportunities. The men trade access to their bodies and to their taste in designer commodities and lifestyle to interact with followers who can financially contribute to dictate the format of the photos available for private or public consumption.